Phytochemical Analysis of Some Fern Species from Satpuda (Khandesh) region, Maharashtra, India. – A Review - Vitthal N. Rathod,; Madhura R. Kadi, (International Journal of Scientific Research in Science and Technology, 2024)
Pteridophytes are vascular cryptogams. The reference to pteridophytes mentioned in various scriptures, like Charak Samhita, but there is no or very little study on phytochemical studies of pteridophytes. The aim of this review is to explore the phytochemical analysis of some pteridophytes. Phytochemical analysis of different pteridophytes revealed a wide range of phytochemicals like alkaloids, flavonoids, terpenoids, etc.
Keywords: Pteridophytes; Antimicrobial; Phytochemical; Satpuda